ANALISIS KEUNTUNGAN USAHA â€œCAFÃ‰ ABCâ€ DI KECAMATAN MALALAYANG KOTA MANADO (Profit Analysis of â€œABC CafÃ© â€ Business In Malalayang Sub-District, Manado City) - Meilan A. Palar; Agnes Loho; Noortje M. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to analyze the business of Cafe ABC in Malalayang Sub District, Manado City. The study was carried out for three months, from November to January 2021.The sampling method was purposive sampling, This sample taker was done deliberately to the owner of Cafe ABC. The data used in this research is primary data which is obtained by direct interviews with the cafe owner. To know the advantages of Cafe ABC use profit analysis.The research results showed that Cafe ABC offers 5 coffee variants, namely 1) Japanese iced, 2) Vietnamese drip hot, 3) Vietnamese drip iced, 4) Kopsus koleps koleps, 5) Yoi kopsus yoi. Each cup has a profit of 1) Rp 14,928, 2) Rp 4,928, 3) Rp 4,928, 4) Rp 11,928, and 5) Rp 11,928. Sales in a week were 369 cups and earned a profit of Rp 2,829,470. The most favorite coffee variant at ABC Cafe is Vietnamese drip iced.